Design of Pneumatic System Simulator when Bleed Leak occurs on ATR 72-590/600 Aircraft as Learning Support at Aviation Polytechnic Surabaya - Putika Sari, Granita; Dwi Cahyo, Bayu; Faizah, Fiqqih (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The aircraft has a bleed air leak detection system that functions as a leak detector on the bleed air duct. If there is a leak in the area around the duct, it will be detected, because it is already equipped with a sensing element. If there is a leak around the bleed air duct, it is characterised by reduced air pressure from the minimum standard. This will be detected by the sensing element installed on the wing, pylon and fuselage. By using Arduino nano and an air pressure sensor as a sensor used when a Bleed Leak occurs and using an indicator lamp as an indicator light when a leak occurs, so that when there is a pressure less than the specified standard, the indicator lamp will light up as an indication of a leak. The reason is because there is a system failure in bleed air leak detection, which is a logic fault, lost continuity, disconnected thermistor, elector static, short circuit, control, component dislocation, fault in the connector and corrosion.